Sex- and Dose-Dependent Differences in the Development of an Addiction-Like Phenotype Following Extended-Access Fentanyl Self-Administration - Towers, Eleanor Blair; Setaro, Ben; Lynch, Wendy J. (Frontiers in Pharmacology, 2022)
Opioid use disorder (OUD) is a major epidemic in the United States and fentanyl is a major culprit. The National Institute on Drug Abuse has highlighted an urgent need for research on risks and outcomes of OUD with fentanyl; a better understanding of sex/gender differences is also critically needed given that the opioid epidemic has been particularly impactful on women. In response to this need, we developed a rat model of OUD with fentanyl and showed that sex impacts relapse vulnerability following extended-access self-administration under a low fentanyl-dose. Here, our goal was to determine sex-differences across a broad dose range, including high doses expected to maximize the expression of addiction-like features (e.g., vulnerability to relapse and physical dependence). Male and female rats were assigned to self-administer one of four fentanyl doses (0.25, 0.75, 1.5, 3.0 µg/kg/infusion), and once they acquired, they were given extended (24-h/day), intermittent-access (2, 5 min trials/hr, fixed-ratio 1) to fentanyl for 10 days. Physical dependence (spontaneous weight loss) was assessed during early withdrawal and relapse vulnerability was assessed on withdrawal-day 15 using an extinction/cue-induced reinstatement procedure. Despite markedly higher intake in the high- versus low-dose groups, each group responded similarly during relapse testing (extinction and cue-induced reinstatement). However, number of infusions, or frequency of use, during extended-access was predictive of later vulnerability to relapse; whereas, total intake impacted physical dependence given that weight loss only occurred following the discontinuation of fentanyl self-administration at the three highest doses. Females self-administered more fentanyl each day and within each binge (active trial) and had longer lasting weight loss during withdrawal than males. Relapse vulnerability was also higher in females than males and highest in females tested during estrus. These findings indicate that sex is an important risk factor for patterns and levels of fentanyl intake, relapse, and physical dependence, and while fentanyl intake predicts physical dependence, frequency of use predicts relapse.